2007
DOI: 10.1016/j.jacc.2006.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptor-1 Blocker Inhibits Atherosclerotic Changes and Endothelial Disruption of the Aortic Valve in Hypercholesterolemic Rabbits

Abstract: Atherosclerotic changes in the aortic valves of rabbits fed with cholesterol were inhibited by ARB, whereas endo-thelial integrity was preserved and transdifferentiation into myofibroblasts and/or osteoblasts in valve leaflets was inhibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 33 publications
(41 reference statements)
4
72
0
3
Order By: Relevance
“…21,22 An experimental study showed that in hypercholesterolemic rabbits, ARBs prevented lesion formation in the aortic valve, specifically preventing the accumulation of macrophages, myofibroblasts and osteoblasts, upregulation of osteopontin and ACE, and disruption of endothelial integrity. 23 Findings from these earlier studies and this study suggest that ARBs prevent progression of CAVD during the early stage. However, use of ACE inhibitors did not affect CAVD progression in this study.…”
Section: Prognostic Factors For Progression Of Early-stage Cavdsupporting
confidence: 53%
“…21,22 An experimental study showed that in hypercholesterolemic rabbits, ARBs prevented lesion formation in the aortic valve, specifically preventing the accumulation of macrophages, myofibroblasts and osteoblasts, upregulation of osteopontin and ACE, and disruption of endothelial integrity. 23 Findings from these earlier studies and this study suggest that ARBs prevent progression of CAVD during the early stage. However, use of ACE inhibitors did not affect CAVD progression in this study.…”
Section: Prognostic Factors For Progression Of Early-stage Cavdsupporting
confidence: 53%
“…16,17,27 Interestingly, treatment with an angiotensin receptor antagonist, olmesartan, inhibited aortic valve leaflet Runx2/Cbfa1 upregulation and macrophage accumulation in the latter study. 27 As noted previously, phosphate induces vesicle formation in myofibroblasts. 67 In vascular smooth muscle cells, this effect of phosphate is mediated by its binding to the sodium-dependent phosphate cotransporter Pit1, which upregulates Runx2/Cbfa1.…”
Section: Calcificationmentioning
confidence: 61%
“…76 The Runx/Cbfa1 transcription factor is increased in aortic valves of 2 hypercholesterolemic rabbit models. 16,17,27 Interestingly, treatment with an angiotensin receptor antagonist, olmesartan, inhibited aortic valve leaflet Runx2/Cbfa1 upregulation and macrophage accumulation in the latter study. 27 As noted previously, phosphate induces vesicle formation in myofibroblasts.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…6,7,37,38 On the other hand, ARBs usually inhibit TGF-b1-CTGF signaling and OPN activity, but do not affect MMP-2 or MMP-9 activity. [39][40][41][42] Thus, Telmisartan is a unique ARB that possesses potent anti-fibrotic activity via inhibition of MMP activation, OPN expression and TGF-b1-CTGF signaling.…”
Section: Discussionmentioning
confidence: 99%